2017
DOI: 10.1111/cxo.12521
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diquafosol three per cent ophthalmic solution on tear film and corneal aberrations after cataract surgery

Abstract: Peri-operative application of diquafosol three per cent ophthalmic solution may prevent dry eye-related ocular surface changes accompanied by improvement of ocular symptom. No definite changes in corneal aberrations were noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…With the emergence of new aqueous tears and/or mucin secretagogue eye drops containing diquafosol sodium (Diquas) or rebamipide (Mucosta) and based on the accumulating evidence in relation to their favorable effects on the tear film and ocular surface epithelium, 5 31 we took further steps to emphasize the importance of a stable tear film of dry eye patients in Asia. These two eye drops work to increase tear breakup time by increasing aqueous and or mucin components to the ocular surface.…”
mentioning
confidence: 99%
“…With the emergence of new aqueous tears and/or mucin secretagogue eye drops containing diquafosol sodium (Diquas) or rebamipide (Mucosta) and based on the accumulating evidence in relation to their favorable effects on the tear film and ocular surface epithelium, 5 31 we took further steps to emphasize the importance of a stable tear film of dry eye patients in Asia. These two eye drops work to increase tear breakup time by increasing aqueous and or mucin components to the ocular surface.…”
mentioning
confidence: 99%
“…The tear film is a remarkable factor of post-operative visual performance after phacoemulsification [34][35][36][37][38][39][40] which also needs to be considered. Tear film instability and inappropriate quality is known to adversely affect image quality [45,46].…”
Section: Plos Onementioning
confidence: 99%
“…The quality of the tear film has a prominently important role in the post-operative outcome after phacoemulsification with IOL implantation. Post-operative use of artificial tears [34,35], diquafosol ophthalmic solution 3% [36,37] and bandage contact lens [38] was found to improve the quality of the tear film in pseudophakic patients. Dry eye was reported to be the second or third most important reason of dissatisfaction after multifocal intraocular lens implantation [39,40].…”
Section: Introductionmentioning
confidence: 95%
“…The postoperative use of cyclosporine 0.05% topical eye drops has led to improvement in dry eye symptoms and visual quality following cataract surgery 11,12 . Recently, diquafosol sodium ophthalmic solution has also been used for the management of DED after cataract surgery 2,5,6,13 . Diquafosol is a dinucleotide derivative and functions as an agonist of the purinergic P2Y 2 receptor 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Diquafosol is known to stimulate not only mucin secretion from goblet cells but also water secretion from conjunctival epithelial cells and the accessory lacrimal glands 14,15 . Studies have shown that diquafosol is very effective in treating and alleviating symptoms of DED after cataract surgery 2,5,6,13 . Furthermore, several studies have shown that topical diquafosol is more effective for managing DED after cataract surgery than artificial tears 5,6 .…”
Section: Introductionmentioning
confidence: 99%